Dampak COVID-19 terhadap Pengungkapan CSR pada Perusahaan Pertambangan Batubara yang Terdaftar di BEI - Ahmadi, Lusiana Putri; Ersyafdi, Ilham Ramadhan; Ginting, Rafles (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2023)
Disclosure of CSR plays an important role in the company as an information medium that shows how much the company cares for workers, the community and the surrounding environment. Companies engaged in the coal mining business sector are often seen as companies that damage the environment. COVID-19 which is endemic in Indonesia has had many impacts on companies, one of which is CSR. Companies will have to recalculate all forms of CSR programs due to financial conditions and wider targets for CSR beneficiaries. So the purpose of carrying out this study is to find out how the impact of COVID-19 has on CSR disclosure of companies listed on the IDX engaged in this business sector. GRI 403 is a reference for CSR disclosure used in this study which contains occupational safety and health. Based on the criteria, 5 of the 13 companies sampled included ADRO, BUMI, INDY, ITMG, and PTBA. Based on the results of the analysis, the company that disclosed all aspects in 2019 and 2020 is ITMG. BUMI and PTBA consistently disclose nine aspects in 2019 and 2020. Whereas INDY and ADRO there is an increase in disclosure from seven and eight aspects in 2019 to eight and nine in 2020. So it is concluded that COVID-19 has not had a negative impact on disclosure of company CSR activities. In addition, all companies have also contributed through CSR programs to overcome the COVID-19 pandemic in Indonesia.